ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK UMUM SWASTA NASIONAL DEVISA DI BEI PERIODE 2014-2018 - Trifonia Klara Seran; Ida Nuraini; Arfida Boedirochminarni (Jurnal Ilmu Ekonomi, 2021)
The purpose of this study is to analyze the influence of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Operational Costs to Operating Income (BOPO), Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) on profitability measured by Return On Asset (ROA) of National private foreign exchange bank in BEI. The analytical tool used is a combined panel data regression analysis method between the time series data of 2014-2018 and cross-section data  6 National private foreign exchange bank in BEI by using the Common Effects model. The results showed that the CAR had a positive and not significant effect on bank profitability (ROA), NPL had a positive and significant effect on bank profitability (ROA), BOPO had a negative effect and significant to bank profitability (ROA), LDR has negative and not significant effect on bank profitability (ROA)and NIM has a positive and not significant effect on bank profitability (ROA).  value of 0.98 (98%) which means as much as 98% changes in bank profitability can be explained by the independent variables that exist while 2% is explained by other causes outside the research model.